1993
DOI: 10.1149/1.2220912
|View full text |Cite
|
Sign up to set email alerts
|

Effect of  KI  on Improving Copper Corrosion Inhibition Efficiency of Benzotriazole in Sulfuric Acid Electrolytes

Abstract: A synergistic effect exists when BTAH and iodide ions are used together to prevent the corrosion of copper in sulfuric acid. The nature of this effect has been studied systematically by using electrochemical techniques and x‐ray photoelectron spectroscopy. The synergistic effect is due largely to the formation of a film of Cu(IBTA) complex and is probably polymeric in nature. This new complex film greatly depresses copper dissolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(53 citation statements)
references
References 2 publications
0
52
0
1
Order By: Relevance
“…For instance, Zhang et al [16] have shown that synergistic effect exists when 2-mercapto benzimidazole is combined together with iodide ions in the prevention of corrosion of copper in aerated sulphuric acid. Wu et al [17] and Schweinsberg [18] have also shown that benzotriazole and 1-[11, 21-dicarboxyl ethyl]-benzotriazole had synergistic effect with KI on the dissolution of copper in aerated H 2 SO 4 . Also reported is the synergistic influence of poly (4-vinyl pyridine) and potassium iodide on the inhibition of corrosion of mild steel in HCl [19].…”
Section: Introductionmentioning
confidence: 96%
“…For instance, Zhang et al [16] have shown that synergistic effect exists when 2-mercapto benzimidazole is combined together with iodide ions in the prevention of corrosion of copper in aerated sulphuric acid. Wu et al [17] and Schweinsberg [18] have also shown that benzotriazole and 1-[11, 21-dicarboxyl ethyl]-benzotriazole had synergistic effect with KI on the dissolution of copper in aerated H 2 SO 4 . Also reported is the synergistic influence of poly (4-vinyl pyridine) and potassium iodide on the inhibition of corrosion of mild steel in HCl [19].…”
Section: Introductionmentioning
confidence: 96%
“…The effect of temperature on the corrosion rate of copper in 0.5 M HNO 3 solution in absence and presence of different doses of the Euphorbia heterophylla plant extract was studied at different temperatures (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) o C) by weight loss method. It is clear that from Table 1 that the weight loss values increase at all doses with raising the temperature.…”
Section: Eff Ect Of Temperaturementioning
confidence: 99%
“…The constituents may adsorb on the metal/acid solution interface by one and/or more of the following ways: (i) electrostatic interaction of protonated molecules with already adsorbed NO 3 -ions, (ii) donor-acceptor interaction between the π-electrons of the aromatic ring and vacant d-orbital of surface iron atoms, and (iii) interaction between unshared electron pairs of hetero atoms and vacant d-orbital of iron surface atoms. It is well known that the copper surface bears positive charge in acid solution 34 , so it was diffi cult for the protonated molecules to approach the positively charged copper surface (H 3 O + /metal interface) due to the electrostatic repulsion. Thus, inhibition of copper corrosion in 0.5 M HNO 3 was due to the adsorption of extract constituents on the copper surface.…”
mentioning
confidence: 99%
“…Tako na primer, Wu [35] Na 2 SO 4 pri pH = 2,95 koristeći kvarc-kristalnu mikrovagu. Pri tome nalazi da se dodatkom KI rastvorima ovih organskih jedinjenja javlja sinergizam.…”
Section: Slika 1 -Struktura Benzotriazolaunclassified